Electron microscopic changes in the nasal membrane of patients with COVID-19 depending on the clinical form and the period of the disease - E. V. Kryukov; K. V. Zhdanov; K. V. Kozlov; V. Yu. Kravtsov; O. V. Mal’tsev; V. S. Sukachev; P. I. Miklush; M. O. Sokolova; V. V. Sharabkhanov; R. I. Glushakov; V. V. Dvoryanchikov; R. R. Achba; et al. (Журнал инфектологии, 2021)
Given that COVID-19 is a global public health problem and that almost all countries in the world have been severely affected by the COVID-19 pandemic, research is being actively pursued to better understand the effects of the virus on human cells. However, it is not clear what changes are observed in the cells of the main gate of infection – the mucosa of the mouth and the nose at different clinical forms and at different periods of disease. Understanding the ultra-structural cell changes of SARS-CoV-2 targets may help clarify the pathogenic aspects of infection in the lower respiratory tract. In this study, the elements of the life cycle of SARS-CoV-2 virus in the cells of the respiratory epithelium of the nose in patients with COVID-19 were evaluated using electron microscopy for the purpose of detecting the peculiarities of viral activity depending on the form and period of disease. Bioptats of the nasal mucous membrane were taken from COVID-19 patients and subsequently examined by electron microscopy. The severity of structural changes in tissue samples, presence of SARSCoV-2 virus in cells were determined, then bioptats were grouped according to the clinical form of the infection process (inapparent, acute upper respiratory tract infections, viral lung disease) and period of disease. It has been established that the most characteristic changes in the mucous membrane of the nose were observed in the first week of infection caused by SARS-CoV-2 and occurring in the form of acute respiratory disease, while viral lung infections have had the highest virus density in vesicles within cells, the formation of smooth virus-free vesicles is most common in inapparent forms. The data obtained may indicate that the formation of classical virus-induced changes in the respiratory epithelium of the nose mucous (vesicles with viral particles and signs of their release from the cell) is characteristic of localized forms of infection caused by SARS-CoV-2 (respiratory infection of the upper respiratory tract) and in cases of generalized infection (viral infection of the lungs and probably other organs and systems) accumulation of the infectious agent in high concentrations in vesicles.